EVALUASI PELAKSANAAN MODEL PEMBELAJARAN AKTIF, KREATIF, EFEKTIF DAN MENYENANGKAN ( PAKEM ) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA LAZUARDI GLOBAL ISLAMIC SCHOOL, DEPOK - Gamar Al Haddar (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2016)
The purpose of the research is to find out the implementation  base of active, creative and effective learning model on Islamic education subject through some aspects (1) context which covers policy, need, purpose, implementation target, and the PAKEM model development at the senior high level of Lazuardi Global Islamic School Depok (2) input which covers teacher, student, supporting facility and curriculum (3) process which covers the implementation process of PAKEM model (4) product which covers the changing of student’s behaviour, the students’ satisfaction on class learning process, the score of written test and the student’s practice result on Islamic education subject at the senior high level of Lazuardi Global Islamic School, Depok This research is an evaluative research. The instruments used for this research are as follow: (1) document study (2) structured interview (3) observation (4) questionnaire for students and teachers.The result of this research shows that the implementation of active, creative, effective and fun  learning model on Islamic education subject at the senior high level of Lazuardi Global Islamic School, Depok based on context, input and process  evaluation has met a demand of standard reference on government’s regulation number 19 year 2005 regarding the national education standard on article 19. Whereas on product evaluation, specifically on the column part of  students’ final assessment used by the school, it needs a revision related to the cognitive and affective  precentage score. Affective aspect should  have higher percentage since this final assessment is concerned with one of the student’s  satisfaction aspect toward the success gained on Islamic education subject. Besides, the main purpose of Islamic education subject is to set – up noble character on students as a standard reference present in goverment regulation number 19 article 26 subsection 2 concerning graduate competence standard which not only emphasize on intellectual and science aspect but also on the shaping of personality and nobel character on students.